Rotating Leadership and Collaborative Innovation - Davis, Jason P.; Eisenhardt, Kathleen M. (Administrative Science Quarterly, 2011)
Using a multiple-case, inductive study of eight technology collaborations between ten organizations in the global computing and communications industries between 2001 and 2006 this paper examines why some interorganizational relationships produce technological innovations while others do not. Comparisons of more and less innovative collaborations show that high-performing collaborative innovation involves more than possessing the appropriate structural antecedents (e.g., R&D capabilities, social embeddedness) suggested by prior alliance studies. Rather, it also involves dynamic organizational processes associated with collaboration partners’ leadership roles that solve critical innovation problems related to recombination across boundaries. While dominating and consensus leadership processes are associated with less innovation, a rotating leadership process is associated with more innovation. It involves alternating decision control that accesses the complementary capabilities of both partner organizations, zig-zagging objectives that engender deep and broad technological search for potential innovations, and fluctuating network cascades that mobilize different participants who bring variable inputs to recombination. The paper also discusses recombination mechanisms in the organization of collaborative innovation, variations in the performance of dynamic interorganizational ties, and how organizations develop symbiotic relationships that overcome the tendency of long-lived relationships toward inertia.